Isonemal prefabrics with perpendicular axes of symmetry - Thomas R.S.D., (Utilitas Mathematica, 2010)
This paper continues the refinement of Richard Roth's taxonomy of isonemal weaving designs through types 11-32 of the 39 in order to solve three problems for those designs: which designs exist in various sizes, which prefabrics can be doubled and remain isonemal, and which can be halved and remain isonemal.